- #1
- 2,168
- 193
Homework Statement
##(2xy+3y^2)dx-(2xy+x^2)dy=0##
Homework Equations
The Attempt at a Solution
It's a homogeneous equation since
we can write,
##M(x,y)=(2xy+3y^2)## and ##M(tx,ty)=t^2M(x,y)## and ##N(x,y)=(2xy+x^2)## and ##N(tx,ty)=t^2N(x,y)##
since orders of t are same they are homogeneous.
Now I can say that ##\frac {dy} {dx}=g(\frac {y} {x})##
where ##v=\frac {y} {x}##.
Now I think there is kind of 2 ways to solve the equation. First way is just put the y=vx in the main equation and try to solve it like that and later by doing separation we can get the result. But I couldn't find a solution
Here it comes,
##(2xvx+3v^2x^2)dx-(2xvx+x^2)(dvx+vdx)=0##
let's gather the terms with dx and dv and separate them,
##(v^2x^2+2x^2v-x^2v)dx-(2x^3v+x^3)dv=0## which later on I don't know what to do. I know that I should separate them but it seems confusing.
Other way is to write in the from of ##\frac {dy} {dx}=\frac {(2xy+3y^2)} {(2xy+x^2)}##
so ##v+\frac {dv} {dx}x=\frac {(2xy+3y^2)} {(2xy+x^2)}##
but then I couldn't separate them so that we can get ##\frac {y} {x}## in the right side.
Last edited: